HISTORY OF UZBEK MAKOM - Ulasheva Ulasheva (Pascasarjana Institut Seni Indonesia Padang Panjang, 2019)
ABSTRACT The Uzbek National musical art has a very ancient history. It can be known from the perfection of our national compositions, our melodies and songs. As shown by the discoveries of archaeologists and other historical sources, the ancient Khorezm, Bactrian and Sogdian elites had a rich and diverse musical art for several centuries BC. Samples of fine art found in such cities as Ayratan, Tuprokkala, Afrosiab, suggest that music is embedded in different aspects of life and has important social value. This article talks about the antiquity of the Uzbek makoms, especially about the history of Shashmakom. Research method used was historical method. Data were obtained through library research in order to get the historical data of Uzbek makoms. Research results show that Uzbek makom has been through a long journey with its various developments affected by various musical culture of other nations. Keywords: Makom, Shashmaqom, Borbad, Khorezm maqoms, Makoms and Fergana –Tashkent.